Comprehensive Methodology for Ethical-Clinical Analysis (CMECA): A new paradigm for resolving end-of-Life dilemmas - Díaz Pérez, Anderson (Acta Bioethica, 2024)
End-of-life care management presents significant ethical challenges, especially in complex clinical cases such as that of a patient with severe head trauma and multiple complications. Ethical decision-making involves considering the rights, dignity, and preferences of the patient and his or her family, as well as quality of life and relief from suffering. The objective of this research is to design and implement a comprehensive methodology to provide a care plan that respects the dignity and improves the quality of life of patients at the end of life, aligned with their wishes and those of their family. The approach used was the Comprehensive Methodology of Clinical-Ethical Analysis (CMECA), which included a continuous evaluation, pain and symptom management, supportive care, limitations of medical interventions, and preparation for the end of life, with the active participation of the family from a palliative care approach. The resolution of the case was achieved through a shared decision between the parents and the medical team, proceeding with a gradual disconnection of life support. The importance and relevance of the Comprehensive Methodology of Ethical-Clinical Analysis (CMECA) is highlighted, due to its comprehensive approach focused on the patient and in accordance with medical ethics. This method stands out for considering legal and ethical aspects, empathy, and respect for human dignity at all times.